OPTIMALISASI ENZIM UREASE UNTUK MENINGKATKAN KAPASITAS DUKUNG TANAH LUNAK - Suparman, Suparman; Rabinah, Aiun Hayatu; Satriyadi, Lilik; Sudarmono, Sudarmono; Warsiti, Warsiti (Politeknik Negeri Semarang, 2024)
The main problems with soft clay soil are high water content, low soil mineral content, and high compressibility, so stabilization materials are needed that can increase the bearing capacity of soft soil. In this research, the urease enzyme was used as a catalyst to increase the bearing capacity of the soil. The material used is organic material, namely soybean powder. The stabilization materials used are urea (CHâ‚„Nâ‚‚O), calcium chloride (CaCl2), and soybean powder (urease enzyme), which will form a lime compound so that it functions as a catalyst for adhesive in stabilizing soft soil. This research aims to improve soft soil by stabilizing it using the SICP (Soybean Induced Calcite Precipitation) method. The variations in urea and CaCl2 concentrations used were 1 mol/L, 2 mol/L, 3 mol/L, 4 mol/L, and 5 mol/L. The soybean extract concentrate used was 30% with a curing time of 7 days. The most optimal test result and what is used is 3 mol/L. This is in line with the SEM and XRD test results. Test specimens were made and cured for 7, 14, 21, and 28 days and then tested for unconfined compressive strength (UCS) to determine the effect of adding calcium carbonat on soil strength. The UCS test shows that the optimum shear strength value of soil cemented with calcium carbonat is produced in a curring period of 14 days is 1.02 kg/cm2. Meanwhile, for a curring period of more than 14 days, the increase in the unconfined compressive strength value is relatively very small. The increase in soil compressive strength after stabilization was 30.77%. The compressive strength value of the soil increases due to the presence of calcium carbonat formed between the soil grains.